2020
DOI: 10.1097/cce.0000000000000125
|View full text |Cite
|
Sign up to set email alerts
|

Critical Care Clinician Reports on Coronavirus Disease 2019: Results From a National Survey of 4,875 ICU Providers

Abstract: Importance: Global cases of coronavirus disease 2019 infection continue to increase, and significant numbers of patients are critically ill, placing an immense burden on ICU resources. Understanding baseline resource needs and surge capacity in the ICU will be essential to meet current and projected healthcare needs. Continued appraisal of the state of readiness for healthcare systems at individual, regional and national levels will be paramount to ensure we are poised to continue the fight agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 8 publications
1
34
0
1
Order By: Relevance
“…For example, providers in North America reported higher levels of emotional distress or burnout, despite reporting fewer shortages of resources, and were also more likely to base CPR and other critical decisions on family wishes compared with findings in other world regions. Our results, which underscore the psychological burden on HCPs, complement results in recent reports about provider well-being from China, Italy, and the United States during the pandemic, [18][19][20][21][22] as well as results from studies before the pandemic (3%-50% burnout rates across various types of ICU providers). [23][24][25][26] We found modifiable and nonmodifiable predictors of burnout that may inform targeted interventions to improve provider experiences and protect their mental well-being.…”
Section: Discussionsupporting
confidence: 86%
“…For example, providers in North America reported higher levels of emotional distress or burnout, despite reporting fewer shortages of resources, and were also more likely to base CPR and other critical decisions on family wishes compared with findings in other world regions. Our results, which underscore the psychological burden on HCPs, complement results in recent reports about provider well-being from China, Italy, and the United States during the pandemic, [18][19][20][21][22] as well as results from studies before the pandemic (3%-50% burnout rates across various types of ICU providers). [23][24][25][26] We found modifiable and nonmodifiable predictors of burnout that may inform targeted interventions to improve provider experiences and protect their mental well-being.…”
Section: Discussionsupporting
confidence: 86%
“…Accordingly, our results demonstrated a correlation between higher income levels of the countries HCWs live in and anxiety scores. Interestingly, a study among 4875 ICU healthcare workers in the US revealed that they were more concerned about facility preparation than about their salary or personal benefits [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since COVID-19 was first detected in the United States in January 2020, more than 500,000 American adults have died of this disease. [1][2][3] Children have been less directly affected by the disease, accounting for < 5% of cases and rarely requiring hospitalization, developing critical illness, or dying of COVID-19. 2,[4][5][6][7][8][9] However, the indirect impact of the COVID-19 pandemic on children's overall health and on the development of critical illness is unclear.…”
mentioning
confidence: 99%
“…Psychosocial stressors may have led to an increase in child abuse, intentional ingestions, and suicide attempts. 2 Severe infections, traumatic injuries, perioperative conditions, and acute exacerbations of chronic illnesses such as asthma and diabetes are among the most common causes of admission to a PICU; thus, the epidemiology of pediatric critical illness was likely sensitive to the indirect effects of COVID-19.…”
mentioning
confidence: 99%